P187 Secukinumab significantly decreased joint synovitis measured by Power Doppler ultrasonography in biologic-naive patients with active psoriatic arthritis: primary (12week) results from a randomised, placebo-controlled Phase 3 study. (26th April 2021) - D'Agostino, Maria-Antonietta; Schett, Georg; Rodríguez, Alejandra López; Šenolt, Ladislav; Maldonado-Cocco, Jose; Burgos-Vargas, Ruben; Naredo, Esperanza; Carron, Philippe; Boers, Maarten; Duggan, Anne-Marie; Goyanka, Punit; Gaillez, Corine
Abstract: Background/Aims   Power Doppler (PD) ultrasonography (PDUS) is a sensitive, non-invasive imaging technology used to assess joint synovitis and enthesitis in psoriatic arthritis (PsA). The European Alliance of Associations for Rheumatology (EULAR) and the Outcome Measures in Rheumatology (EULAR-OMERACT) developed a standardised ultrasonography composite scoring system that is sensitive to change (the global EULAR-OMERACT synovitis score [GLOESS]) to detect and score joint synovitis. We report primary (12-week) efficacy and safety data from ULTIMATE (NCT02662985), the first large, randomised, double-blind, placebo-controlled Phase 3 study to assess the time course of response to subcutaneous secukinumab on joint synovitis with PDUS in PsA. Methods   This 52-week study has a 12-week double-blind treatment period followed by 12week open-label and 6-month open-label extensions. The study recruited biologic-naive patients with active PsA and inadequate response to conventional disease-modifying antirheumatic drug(s), with joint synovitis on PDUS (≥1 joint [of 48] with both total synovitis PDUS score and PD signal ≥2; or ≥ 2 joints with PDUS score ≥2 and PD signal ≥1) at screening and baseline and ≥1 clinical enthesitis site at baseline. Patients received secukinumab (300 or 150 mg) or placebo weekly followed by 4-weekly dosing (from Week 4). The primary endpoint was the difference in mean change in GLOESS from baseline to Week 12 between secukinumab and placebo, determined by mixed-effects model repeated measures analysis. Safety analyses included all patients who received ≥1 dose of study treatment. Results   Of 166 patients enrolled, 96% (160/166) completed 12 weeks of treatment (secukinumab: 99% [82/83]; placebo: 94% [78/83]). Baseline demographics, clinical and ultrasound characteristics were similar across treatment groups. The primary endpoint was met; adjusted mean change in GLOESS was significantly higher with secukinumab than placebo (-9.0 vs -5.8; P = 0.004) at Week 12 (Table 1 ), with statistical significance seen as early as Week 1. All key secondary endpoints were met. No new or unexpected safety signals were reported. Conclusion   Secukinumab demonstrated a rapid and significant decrease in synovitis over 12 weeks (per GLOESS), and superior efficacy on ACR20/50 responses and SPARCC enthesitis vs placebo at Week 12 in biologic-naive patients with PsA. The safety profile of secukinumab was consistent with previous reports. Disclosure   M. D'Agostino: Honoraria; M-A.D has received speaker/consultancy fees from Sanofi, Novartis, BMS, Celgene, Roche, AbbVie, UCB and Eli Lilly. G. Schett: Honoraria; G.S. has received honoraria from AbbVie, BMS, Celgene, Janssen, Lilly, Novartis, Roche and UCB. A. López Rodríguez: Corporate appointments; A.L.R. is a clinical trial researcher, speaker and consultant for Roche, Eli Lilly, Novartis, BMS and Neovacs. L. Šenolt: Honoraria; L.S. has received speaker's honoraria from AbbVie, Amgen, BMS, Celgene, Eli Lilly, MSD, Novartis, Pfizer, Roche and UCB., L.S. has received expenses for attendance at advisory board meetings from AbbVie, BMS, Celgene, MSD, Novartis, Pfizer, Roche and UCB., L.S. has received honoraria for clinical trials from AbbVie, Amgen, BMS, Celgene, Novartis, Pfizer, Takeda and UCB. Grants/research support; L.S. has received research grants from AbbVie. J. Maldonado-Cocco: Consultancies; J.M-C. is a speaker/consultant for Pfizer, Merck Sharp & Dohme, Sanofi-Aventis, Novartis, BMS, Roche, Boehringer Ingelheim, Schering-Plough, Abbott, UCB, Eli Lilly and Gilead. Other; J.M-C. is a clinical researcher as PI in clinical trials for Pfizer, Merck Sharp & Dohme, Sanofi-Aventis, Novartis, BMS, Roche, Boehringer Ingelheim, Schering-Plough, Abbott, UCB, Eli Lilly and Gilead. R. Burgos-Vargas: None. E. Naredo: Honoraria; E.N. has received speaker fees from AbbVie, Roche, BMS, Pfizer, UCB, Lilly, Novartis, Janssen and Celgene GmbH, and honoraria for clinical trials from AbbVie, Novartis and BMS. Grants/research support; E.N. has received research grants from Lilly. P. Carron: Consultancies; P.C. is a speaker/consultant for Pfizer, Merck Sharp & Dohme, Novartis, BMS, AbbVie, UCB, Eli Lilly, Gilead and Celgene Corporation. Grants/research support; P.C. has received research grants from UCB, Merck Sharp & Dohme and Pfizer. M. Boers: Consultancies; M.B. is a consultant for BMS, Novartis, Pfizer, GSK and Mylan. A. Duggan: Other; A-M.D. is an employee of Novartis. P. Goyanka: Other; P.G. is an employee of Novartis. C. Gaillez: Shareholder/stock ownership; C.G. is a shareholder of NVS and BMS. Other; C.G. is an employee of Novartis.